Linguistic Diaspora in Leila Sebbar’s Je ne Parle pas la Langue de mon Père - AMAL EL MANSOURI (International Journal of Linguistics, Literature and Translation, 2025)
This paper examines Leïla Sebbar's autobiographical narrative Je ne parle pas la langue de mon père as a critical exploration of linguistic diaspora and postcolonial identity. Through close textual analysis, the study investigates how Sebbar's inability to speak Arabic—her Algerian father's native language—represents not merely a communicative gap but a profound rupture in cultural inheritance and self-formation. Drawing on Marianne Hirsch's theory of postmemory, the paper analyzes how linguistic absence functions as a form of inherited trauma that shapes diasporic subjectivity across generations. The analysis unfolds in three sections: first, situating Sebbar's experience within the historical context of French colonial language policies in Algeria that systematically marginalized Arabic; second, examining the emotional and psychological dimensions of linguistic loss as manifested in feelings of guilt, fragmentation, and cultural dislocation; and third, exploring how Sebbar transforms this absence into narrative resistance by appropriating French—the colonizer's language—to articulate silenced histories and reclaim hybrid postcolonial identity. The paper demonstrates that Sebbar's memoir challenges essentialist notions of linguistic authenticity while revealing how literature can serve as a site of testimony and cultural reclamation in the aftermath of colonial trauma.